Tacrolimus Bayesian Dose Adjustment in Pediatric Renal Transplant Recipients. Issue 4 (August 2021) - Marquet, Pierre; Cros, Florine; Micallef, Ludovic; Jacqz-Aigrain, Evelyne; Woillard, Jean-Baptiste; Monchaud, Caroline; Saint-Marcoux, Franck; Debord, Jean
Abstract : Background: Immunosuppressant Bayesian Dose Adjustment (ISBA) is an online expert system that estimates the area under the curve (AUC) of immunosuppressive drugs through pharmacokinetic modelling and Bayesian estimation to propose dose adjustments to reach predefined exposure targets. The ISBA database was retrospectively analyzed to describe tacrolimus pharmacokinetics and exposure, evaluate the efficiency of ISBA dose recommendations, and propose tacrolimus AUC0–12h target ranges for pediatric renal allograft recipients treated with immediate release tacrolimus. Methods: The database included 1935 tacrolimus dose adjustment requests from 419 patients <19 years old who were treated with immediate-release tacrolimus and followed in 21 French hospitals. The tacrolimus exposure evolution with patient age and posttransplantation time, the correlation between trough tacrolimus concentration (C0 ) and AUC0–12h at different periods posttransplantation, and the efficiency of dose recommendations to avoid underexposure and overexposure and to decrease between-patient AUC variability were investigated. Results: Tacrolimus AUC showed large between-patient variability (CV% = 40%) but moderate within-patient variability (median = 24.3% over a 3-month period). Dose-standardized exposure but not the AUC/C0 ratio significantly decreased with time posttransplantation and patient age. We derived AUC0–12h ranges from the consensual C0 ranges using linear regression equations. When the ISBA recommended dose was applied, the AUC distribution was narrower and a significantly higher proportion was within the targets ( P < 0.0001). Conclusions: ISBA efficiently reduced tacrolimus underexposure and overexposure. The AUC0–12h target ranges for pediatric patients derived from the database were similar to those previously reported for adults. Estimating the AUC/C0 ratio could help determine personalized C0 targets. Abstract : Supplemental Digital Content is Available in the Text.